PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL TERHADAP AKUNTABILITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN ACEH UTARA - Eldis Ramdani; Neo Agustina (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2019)
This study aims to examine the effect of the implementation of accrual-based government accounting standards on the accountability of financial statements of the North Aceh District Government. The data used in this study are primary data as many as 70 samples with purposive sampling technique. The method used to analyze the independent variables with the dependent variable is a simple linear regression method and a classic assumption test. The results of the study are partial, the application of accrual-based government accounting standards has a significant influence on the accountability of financial statements in the North Aceh District Work Unit.